2009
DOI: 10.1007/978-3-642-05258-3_56
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Methods for Many-Objective Optimization

Abstract: Abstract. An important issue with Evolutionary Algorithms (EAs) is the way to identify the best solutions in order to guide the search process. Fitness comparisons among solutions in single-objective optimization is straightforward, but when dealing with multiple objectives, it becomes a non-trivial task. Pareto dominance has been the most commonly adopted relation to compare solutions in a multiobjective optimization context. However, it has been shown that as the number of objectives increases, the convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…An increase in the number of objectives causes a large portion of a randomly generated population to become non-dominated [28]. Having a population which is largely composed of non-dominated solutions does not give room for creating new solutions in every generation [3,13].…”
Section: Non-dominated Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the number of objectives causes a large portion of a randomly generated population to become non-dominated [28]. Having a population which is largely composed of non-dominated solutions does not give room for creating new solutions in every generation [3,13].…”
Section: Non-dominated Populationmentioning
confidence: 99%
“…Most of the EMO algorithms use the concept of Pareto Dominance in order to compare and identify the best solutions [28]. An increase in the number of objectives causes a large portion of a randomly generated population to become non-dominated [28].…”
Section: Non-dominated Populationmentioning
confidence: 99%
“…The experimental results showed that average ranking is a good method. Garza-Fabre et al [26] proposed three ranking methods, two based on the difference of objective values between individuals and one based on the distance to the ideal point.…”
Section: Ranking and Modified Pareto Dominancementioning
confidence: 99%
“…The second direction is to improve the weak selective pressure of dominance-based selection when facing the large number of non-dominated solutions in the population. The techniques may modify Pareto dominance or assign different ranks to non-dominated solutions [20][26]. The third direction is to try selection mechanisms other than dominance-based ones, such as adopting performance indicators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The ranking method is called global detriment (GD) and has been proposed by the same authors of the CEGA in[17]. The global detriment is a ranking method based on distances objective-wise between the individual and the others individuals of the population.…”
mentioning
confidence: 99%